Quantifying the Distribution of Electrolyte Decomposition Products in Silicon-Graphite Electrodes by Neutron Depth Profiling. Issue 10 (1st January 2018) - Wetjen, Morten; Trunk, Markus; Werner, Lukas; Gernhäuser, Roman; Märkisch, Bastian; Révay, Zsolt; Gilles, Ralph; Gasteiger, Hubert A.
Abstract : Silicon-based anodes for lithium-ion batteries exhibit severe volumetric changes of the active material particles during (de-)lithiation, resulting in continuously occurring side reactions at the silicon/electrolyte interface over extended charge/discharge cycling. The thus formed and accumulating electrolyte decomposition products lead to a growth of the solid-electrolyte-interphase (SEI) on the silicon particles. This results not only in an ongoing loss of electrolyte but also in a significant swelling and impedance increase of silicon-based anodes which significantly compromises their cycle-life. In the present study, neutron depth profiling (NDP) is used post mortem as a non-destructive, highly lithium-sensitive technique to (i) quantify the amount of lithium-containing electrolyte decomposition products in silicon-graphite (SiG) electrodes (35 wt% silicon, areal capacity ∼1.7 mAh cm −2 ), (ii) monitor their distribution across the SiG electrode thickness, and (iii) determine the active material utilization across the electrode over 140 cycles. Hence, SiG negative electrodes are aged and characterized by means of galvanostatic cycling in SiG//LiFePO4 pseudo-full cells, using a capacitively oversized positive electrode and an electrolyte mixture consisting of 1 M LiPF6 in EC:EMC with 5 wt% FEC. High-resolution cross-sectional SEM images and post-mortem characterization of the SiG electrodes with respect to changes in electrode mass thickness complement the analysis.